Subchronic and acute preclinic toxicity and some pharmacological effects of the water extract from leaves of Petiveria alliacea (Phytolaccaceae) - García González, Mildred (Universidad de Costa Rica, 2006)
We tested the effects of the aqueous extract of Petiveria alliacea leaves on acute and sub-chronic toxicity, hematocrit and blood glucose level and intestinal motility of male albino NGP mice of 20 to 25 g mean weight. Treatments were in all cases doses of 1 000 and 2 000 mg/kg animal weight and a control treatment with 0.5 ml distilled water, using 10 animals per treatment and administered orally every day (5 days per week). Experimental periods were 18 and 70 days for acute and sub chronic toxicity, respectively. No mortality nor any toxicity signs could be observed. A slight but significant increase in the glucose levels during the first three weeks was observed with the 1 000 mg/kg dose but not for the higher 2 000 mg/kg dose. After administering the doses once after a starving period of six hours, no significant differences in intestinal motility could be found.